Association between JAK2 rs4495487 Polymorphism and Risk of Budd-Chiari Syndrome in China - Peijin Zhang; Yanyan Zhang; Jing Zhang; Hui Wang; He Ma; Wei Wang; Xiuyin Gao; Hao Xu; Zhaojun Lu (Gastroenterology Research and Practice)
Myeloproliferative neoplasms (MPNs) are the leading cause of Budd-Chiari syndrome (BCS), and the C allele of JAK2 rs4495487 was reported to be an additional candidate locus that contributed to MPNs. In the present study, we examined the role of JAK2 rs4495487 in the etiology and clinical presentation of Chinese BCS patients. 300 primary BCS patients and 311 healthy controls were enrolled to evaluate the association between JAK2 rs4495487 polymorphism and risk of BCS. All subjects were detected for JAK2 rs4495487 by real-time PCR. Results. The JAK2 rs4495487 polymorphism was associated with JAK2 V617F-positive BCS patients compared with controls (P<0.01). The CC genotype increased the risk of BCS in patients with JAK2 V617F mutation compared with individuals presenting TT genotype (OR = 13.60, 95% CI = 2.04–90.79) and non-CC genotype (OR = 12.00, 95% CI = 2.07–69.52). We also observed a significantly elevated risk of combined-type BCS associated with CC genotype in the recessive model (OR = 4.44, 95% CI = 1.31–15.12). This study provides statistical evidence that the JAK2 rs4495487 polymorphism is susceptibility factor JAK2 V617F positive BCS and combined BCS in China. Further larger studies are required to confirm these findings.